Cross-border health services – selected issues - Paulina Jaszczuk (Journal of Geography, Politics and Society, 2018)
One of the superior principles in integrated Europe is free flow of persons, services and capital. An expression of this freedom are regulations about coordination of social security systems binding both in EU and EFTA member states. The principles of granting health services and their scope are determined by the provisions about coordination of social security systems. In the article I will try to discuss the most important regulations regarding the issues related to cross-border health care, both EU regulations and the related provisions of the domestic law.